ASSESSMENT ON ANTIMICROBIAL PROPERTIES OF SURFACTIN FROM BACILLUS SUBTILIS ON PROTOPLASTS AND SPHEROPLASTS OF PATHOGENIC BACTERIA - Chitra, B.; Vijayakumar, A. Benno Susai (International Journal of Current Pharmaceutical Research, 2016)
Objective: The aim of this paper is to assessment on antimicrobial properties of surfactin from Bacillus subtilis on protoplasts and spheroplasts of pathogenic bacteria. Methods: Bacillus sp were isolated from the polluted soil samples and these isolates were screened for biosurfactin activity using haemolytic activity. The biosurfactant was also studied for their antibiotic activity and the minimum inhibitory concentration was determined by testing the effect of surfactin on the pathogenic microorganisms. The lytic activity of surfactant was also tested on the protoplasts and spheroplasts of the pathogens. Results: The formation of a clear zone around the colonies and the lysis of erythrocytes shows the antimicrobial and lytic activity of biosurfactants. Conclusion: The results of the current study reveal that surfactin from B. subtilis possesses significant antimicrobial and lytic activity.